Ferdinand Magellan : the first voyage around the world - Burnett, Betty (New York : Rosen Pub. Group's Rosen Central, 2003)
A description of the life and voyage of the sixteenth-century Portuguese sea captain who commanded the first expedition to sail around the world.
Includes Biographical references
10 - 13 years
Keywords: Magalhaes, Fernao de -- d. 1521; Magellan, Ferdinand -- d. 1521. -- Explorers; Explorers -- Portugal -- Biography -- Juvenile Litrature; Voyages around the world -- Juvenile Litrature; Explorers; Voyages around the world